The genome size, chromosome number and the seed adaption to long-distance dispersal of Ipomoea pes-caprae (L.) - Ye, Kangzhuo; Dong, Chunxing; Hu, Bin; Yuan, Jieyu; Sun, Jin; Li, Zixian; Deng, Fang; Fakher, Beenish; Wang, Lulu; Pan, Chenglang; Aslam, Mohammad; Qin, Yuan; et al. (Frontiers in Plant Science, 2023)
IPC is a common species in tropical and subtropical coastal areas and one of the world's most widely distributed plants. It has attracted researchers for its outstanding biological, ecological and medicinal values. It has been reported that the genetic diversity of IPCs located on different continents is very low because of their frequent gene flow. During the long journey of evolution, every aspect of the plant morphologies has evolved to the best adaptivity to the environment, seeking their survival and progeny expansion. However, the fundamental genetic characteristics of IPC and how their seed adapted to the success of population expansion remain unknown. In this study, the fundamental genetic characteristics, including the genome size and the chromosome number of IPC, were investigated. The results showed that IPC's genome size is approximately 0.98-1.08 GB, and the chromosome number is 2n=30, providing the basic information for further genome analysis. In order to decipher the long-distance dispersal secret of this species, the fruit and seed developments, seed morphology, and seed germination were extensively investigated and described. The results showed an exquisite adaptive mechanism of IPC seeds to fulfill the population expansion via ocean currents. The large cavity inside the seeds and the dense tomenta on the surface provide the buoyancy force for the seeds to float on the seawater. The hard seed coats significantly obstructed the water absorption, thus preventing the seed from germination during the dispersal. Meanwhile, the fully developed embryos of IPC also have physiological dormancy. The physical and physiological characteristics of IPC seeds provide insight into the mechanism of their long-distance dispersal across the oceans. Moreover, based on morphological observation and semi-section microscopy, the development pattern of IPC glander trichomes was described, and their physiological functions were discussed.